2018
DOI: 10.1186/s12864-018-4871-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of putative regulatory regions and transcription factors associated with intramuscular fat content traits

Abstract: BackgroundIntegration of high throughput DNA genotyping and RNA-sequencing data allows for the identification of genomic regions that control gene expression, known as expression quantitative trait loci (eQTL), on a whole genome scale. Intramuscular fat (IMF) content and carcass composition play important roles in metabolic and physiological processes in mammals because they influence insulin sensitivity and consequently prevalence of metabolic diseases such as obesity and type 2 diabetes. However, limited inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 79 publications
6
63
0
2
Order By: Relevance
“…Phenotypes from 192 Nelore steers were previously described elsewhere (Cesar et al, 2018;de Lima, 2019). These steers were a subsample from a broader experimental population of 593 steers (de Oliveira et al, 2014) for which muscle RNAseq data were available.…”
Section: Phenotypic Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Phenotypes from 192 Nelore steers were previously described elsewhere (Cesar et al, 2018;de Lima, 2019). These steers were a subsample from a broader experimental population of 593 steers (de Oliveira et al, 2014) for which muscle RNAseq data were available.…”
Section: Phenotypic Datamentioning
confidence: 99%
“…A total of 192 samples from the Longissimus thoracis muscle of Nelore steers were used in this study. The RNA sequencing from these samples was performed at the Genomics Core Facility at ESALQ (Piracicaba, SP, Brazil), as previously described elsewhere (Cesar et al, 2018) and archived on the European Nucleotide Archive (ENA) under accessions: PRJEB13188, PRJEB10898, and PRJEB19421.…”
Section: Rna Sequencing and Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…A usual strategy is the use of molecular markers for genomic selection based on SNPs (single nucleotide polymorphisms) genotyping, which allows the detection of DNA variants associated with FE. However, the majority of the SNPs previously identified in Genome-Wide Association studies (GWAs) and expression quantitative loci (eQTL) association study (10) are non-causal variants (11-13), which are located in intron or intergenic genomic regions. There is an urgent need to establish the functional (causal) variants of this important phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported identi ed genes related to storage lipids in broilers [4,5,6]. On the other hand, the integration of high-throughput genomic DNA and RNA sequencing leads to identify genomic regions that control traits at the whole genome scale [7]. Some studies that using high-density microarrays in two groups of obese (high-fat) and lean (low-fat) birds indicated genes associated with lipogenic pathways [8,9].…”
mentioning
confidence: 99%